Von Willebrand Factor Effect on Pro-Thrombotic State in Sickle Cell Disease - Al-Maaroof, Zainab W. (American Journal of Biology and Natural Sciences, 2025)
Background: sickle cell disease (SCD) is a serious kind of hemolytic anaemia that marked by persistent haemolysis, hypercoagulation, and changes in hemostatic parameters.These variables have the potential to cause thrombosis in SCD patients. Multimeric plasma hemostatic protein von Willebrand factor (VWF), which is produced and secreted by platelets and endothelial cells, is elevated in SCD and rises much more during a vaso-occlusive crisis (VOC). Nevertheless, it is unclear how VWF affects the pathophysiology of VOC. Objective: The purpose of the review is to present a concise scientific summary of thrombotic risk in SCD, which has a significant morbidity and mortality on patient's life. Conclusion: Previous research evaluating these markers indicates that, when comparing SCA to control, there was no discernible difference in VWF Ag, ADAMTS13, or VWF Ag: ADAMTS13 antigen ratio. According to other research, patients' VWF and ADAMTS 13 activity levels were much higher than those of control.